Kemampuan Jus Jambu Biji Merah (Psidium Guajava L.) Dibanding Multivitamin 500 Mg Dalam Mempertahankan Antal Eritrosit Pasca Senam Aerobik High Impact Di Jurusan Jamu Politeknik Kementerian Kesehatan Surakarta - Sigit Tri Ambarwanto; M. Ali Nasikin (Poltekkes Kemenkes Surakarta, 2019)
Background: One of important missions from American Collage of Sports Medicine (ASCM) is to support physical activity in community. During high impact physical activity, oxygen consumption in whole bodies are increasing 20 times. This increasing of oxygen consumption may lead to increase of free radical production that can cause cell damage. One of free radicals, Hydrogen peroxide causes damage in red blood cell (erythrocyte) membrane, with the result decreasing of red blood cell life time, moreover inducing anemia. Substance that can inhibit damage cell caused by free radical called antioxidant. Antioxidants are plentiful in fruit and vegetables, especially colorfull fruits and vegetables. One of fruit that well known as antioxidant source is red guava (Psidium guajava). Red guava containing lycopen which is has high antioxidant activity. The aim of this study is to understand effect of red guava juice treatment to red blood cell serum level in respondent who given physical activity. Standard of comparison in this study is vitamin C (zegavit 500 mg). Method: this study used quasi experiment, independent variable is vitamin C (zegavit 500 mg) and red guava juice treatment, dependent variable is red blood cell serum level. Results: The result of this study showed that there was no decreasing indication in red blood cells serum level of 3 groups. Conclusion: The conclusion in this study is there was no difference between red guava juice and vitamin C (zigavit 500 mg) treatment to avoid decreasing of red blood cells serum level after high impact physical activities.